The iDiv Ecotron—A flexible research platform for multitrophic biodiversity research. Issue 21 (4th October 2021) - Schmidt, Anja; Hines, Jes; Türke, Manfred; Buscot, François; Schädler, Martin; Weigelt, Alexandra; Gebler, Alban; Klotz, Stefan; Liu, Tao; Reth, Sascha; Trogisch, Stefan; Roy, Jacques; et al.
Abstract: Across the globe, ecological communities are confronted with multiple global environmental change drivers, and they are responding in complex ways ranging from behavioral, physiological, and morphological changes within populations to changes in community composition and food web structure with consequences for ecosystem functioning. A better understanding of global change‐induced alterations of multitrophic biodiversity and the ecosystem‐level responses in terrestrial ecosystems requires holistic and integrative experimental approaches to manipulate and study complex communities and processes above and below the ground. We argue that mesocosm experiments fill a critical gap in this context, especially when based on ecological theory and coupled with microcosm experiments, field experiments, and observational studies of macroecological patterns. We describe the design and specifications of a novel terrestrial mesocosm facility, the iDiv Ecotron. It was developed to allow the setup and maintenance of complex communities and the manipulation of several abiotic factors in a near‐natural way, while simultaneously measuring multiple ecosystem functions. To demonstrate the capabilities of the facility, we provide a case study. This study shows that changes in aboveground multitrophic interactions caused by decreased predator densities can have cascading effects on the composition of belowground communities. The iDiv Ecotrons technical features, which allow for the assembly of an endless spectrum of ecosystem components, create the opportunity for collaboration among researchers with an equally broad spectrum of expertise. In the last part, we outline some of such components that will be implemented in future ecological experiments to be realized in the iDiv Ecotron. Abstract : The iDiv Ecotron is a novel and unique research platform that was explicitly designed to address the perpetual claim that biodiversity–ecosystem function (BEF) research in terrestrial ecosystems needs to move beyond the manipulation of diversity at single trophic levels to embrace the multitrophic complexity of ecological communities.